Penerapan Pembelajaran Anak Usia Dini Menggunakan Model Sentra Balok di Tkit Ihya As Sunnah: Early Children's Learning Applicants Using The Beam Center Model At Tkit Ihya As Sunnah - Fany Maulany; Intan Maharani Putri (Universitas Ngudi Waluyo, 2024)
PAUD is an educational institution that has the goal of laying the foundation for growth and development of physical-motor, intelligence, socio-emotional, language, and communication, in accordance with the uniqueness and stages of child development. PAUD is aimed at children aged 0-6 years which is often called the golden age in development or the golden age. The central learning model is based on the assumption that children learn by playing with objects and people around them (environment). Describes the Application of Early Childhood Learning using the Beam Center Model at TKIT Ihya Assunah. Data collection techniques using the method of observation, interviews and documentation. The teacher gives playing time to children for approximately 1.5 hours. After the children play with blocks and have become compatible with their respective buildings, they dismantle the buildings they made in an orderly manner. They really follow the procedures that the school makes. They collect all the blocks they have used first, then call the teacher to count and record by the teacher. When finished, they had to save the blocks they had used. Each of them tidied up their blocks back into the special block cupboard that had been provided by the school. ABSTRAK PAUD adalah sebuah lembaga pendidikan yang meiliki tujuan tujuan untuk peletakkan dasar ke arah pertumbuhan dan perkembangan fisikmotorik, kecerdasan, sosio-emosional, bahasa, dan komunikasi, sesuai dengan keunikan yang dimiliki serta tahapan perkembangan anak. PAUD ditujukan bagi anak usia 0-6 tahun yang sering disebut masa emas dalam perkembangan atau golden age Model pembelajaran sentral didasarkan pada anggapan bahwa anak belajar dengan cara bermain dengan benda-benda dan orang-orang di sekitarnya (lingkungan). Mendeskripsikan tentang Penerapan Pembelajaran Anak Usia Dini menggunakan Model Sentra Balok di TKIT Ihya Assunah. Teknik pengumpulan data menggunakan metode observasi, wawancara dan dokumentasi. Guru memberikan waktu bermain kepada anak selama kurang lebih 1,5 jam. Setelah anak bermain balok dan telah menjadi sesuai bangunannya masing-masing, mereka membongkar bangunan buatan mereka dengan tertib. Mereka sangat mengikuti prosedur yang sekolah buat. Mereka mengumpulan semua balok yang telah mereka pakai terlebih dahulu, lalu memanggil guru untuk menghitung dan di catat oleh guru. Setelah selesai, mereka harus menyimpan balok-balok yang telah mereka pakai. Masing-masing merapihkan kembali balok-balok nya ke lemari khusus balok yang telah disediakan oleh sekolah.